El desarrollo de las microhabilidades como requisitos para lograr la comprensión del texto, en los estudiantes del 7mo año de educación básica de la Escuela Rafael J. Bazante, del cantón Chimbo, provincia de Bolívar, el período 2010 – 2011 - Morales Villena, Moisés Hidalgo (2011)
In the process of professionalisation, the University, according to the laws requires the development of a research work prior to graduation, which is why we decided to work with children in our school, in a new aspect, that relates to the Updating and Strengthening General Education Curriculum of Basic, such as microskills, the same as those based on simple elements, like molecules consist of atoms, because the skills needed to be able microskills to complete. They tend to fail more often because they need specific habits, behaviors consistent, especially because they behave in part as the "skills", requiring a remarkable will and exercise. After completion of the work is structured as follows: the first part is related to the topic: The development of microskills as requirements to develop an understanding of the text in the 7th year students in the Basic Education School "Rafael J. Bazante "of the parish of St. Joseph, Canton Chimborazo, Bolívar province in the period 2010 - 2011, are the background, the problem, the rationale, objectives and finally the hypothesis, variables and operationalization of the variables. The first chapter concerns the theoretical scientific information that supports research, which is why we consider the microskills that are generally easy to identify and learn, and produce notable successes with little effort, so that these partial successes to encourage extra students to pursue and complete operating small learning they will be useful in many places. These microskills should be developed in the area of language arts, to strengthen macrodestrezas, being one of the main reading, which is a learning tool and / or recreation that is known and has been used throughout all times and throughout the world. Must employ techniques to achieve reading comprehension. One of the simplest exercises it is the synthesis, because it attempts to reduce the summary by each student to a single sentence, while the other technique, paraphrasing involves not reduce, but to change the expression, in words of each reader. We also find the apostille, which is to clarify, discuss, explain, amplify or provide extra information that the caller requires to the understanding of speech. The important thing is to develop understanding, since it is the process of making meaning, learning relevant ideas of a text and relating them to ideas they already have. For this the reader must "interact" with the text. Reading is a process of interaction between thought and language, the reader needs to recognize letters, words, phrases, however when reading does not always understand the message contained in the text, our mentality is not enough for both honestly, it is even possible to misunderstand, as almost always happens. In the second chapter we find the methodological strategies, which are spelled out the types of research that will develop at work, the sample, instruments and research techniques and methods. The third chapter is the analysis of the results, because the answers to each question are transferred to the statistical tables and then represented in statistical graphics, to proceed to the analysis of results, and then to do the testing of the hypothesis; the conclusions and recommendations. Finally, the fourth chapter we have the proposal, which contains a title, introduction, objectives that are to be achieved, the very development of the proposal, which is explained in detail as the different techniques used to enable the development of microskills; is followed by verification of the application. All this culminates in the bibliography and appendices.